2017
DOI: 10.3727/096504016x14783677992682
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA Taurine-Upregulated Gene 1 Promotes Cell Proliferation and Invasion in Gastric Cancer via Negatively Modulating miRNA-145-5p

Abstract: Long noncoding RNA (lncRNA) taurine-upregulated gene 1 (TUG1) is involved in the development and carcinogenesis of various tumors, suggesting the diagnostic potential of TUG1 in these cancers. However, the exact role of TUG1 and its underlying mechanism in gastric cancer (GC) remain unknown. In this study, the expression of TUG1 and miR-145-5p in GC cell lines and nonmalignant gastric epithelial cell lines was detected by qRT-PCR. BGC-823 and SGC-7901 cells were transfected with si-TUG1, pcDNA 3.1-TUG1, miR-14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 20 publications
0
36
0
1
Order By: Relevance
“…Liu et al showed the tumor‐promoting role of HOTAIR in gastric cancer progression through positively regulating HER2 expression by sponging miR‐331‐3p. In addition, expression of several miRNAs, including miR‐675, miR‐145‐5p, miR‐152, miR‐145, miR‐23b‐3p, and miR‐335‐5p, are significantly dysregulated by lncRNAs and then change the expression of target mRNAs in gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al showed the tumor‐promoting role of HOTAIR in gastric cancer progression through positively regulating HER2 expression by sponging miR‐331‐3p. In addition, expression of several miRNAs, including miR‐675, miR‐145‐5p, miR‐152, miR‐145, miR‐23b‐3p, and miR‐335‐5p, are significantly dysregulated by lncRNAs and then change the expression of target mRNAs in gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al 32 showed the tumor-promoting role of HOTAIR in gastric cancer progression through positively regulating HER2 expression by sponging miR-331-3p. In addition,expression of several miRNAs, including miR-675,33 miR-145-5p,34…”
mentioning
confidence: 99%
“…In a ceRNA model, lncRNA release or upregulate target mRNA of miRNAs by competitively binding with the same miRNAs Zhang et al [27][28][29][30][31]. TUG1 participates in the progression and development of multiple tumors by acting as a ceRNA Zhang et al [22,24,26,[32][33][34][35][36]. To determine whether TUG1 acts as a ceRNA in HCC, we applied bioinformatics analysis (http://starbase.sysu.edu.…”
Section: Tug1 Regulates Zeb1 By Competitively Binding With Mir-142-3pmentioning
confidence: 99%
“…The lncRNA taurine upregulated gene 1 (TUG1) plays a role in the progression of several human cancers by interacting with miRNAs Wang et al [22][23][24]. For example, TUG1 accelerates the malignancy of pancreatic cancer through sponging miR-382 Zhao et al [25], mediates methotrexate resistance in colorectal cancer (CRC) by interacting with miR-186 Li et al [26], acts as an oncogene in osteosarcoma by binding with miR-335 Wang et al [22], and improves gastric cancer progression through sponging miR-145-5p Ren et al [24]. Thus, this study aimed to clarify the interaction between TUG1 and miR-142-3p in HCC.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro, knock‐down of TUG1 induced cell apoptosis and suppressed both cell proliferation and invasion. Studies investigating tumours from other anatomical sites showed that TUG1 can act as a miR‐26a sponge to regulate human glioma cell proliferation (Li, An, Zhang, & Ma, ); it directly binds miR‐145‐5p in gastric (Ren, Li, Li, Zhang, & Han, ) and in bladder cancer cells exerting a double‐negative feedback loop between TUG1 and miR‐145 (Tan, Qiu, Li, & Liang, ). Nevertheless, we do not have data from in vitro studies addressing TSCC/OSCC.…”
Section: The Endogenous Rna Networkmentioning
confidence: 99%